Review of Pedagogical Knowledge Through the Use of GeoGebra for Junior High School Students in Improving Learning Outcomes on Straight Line Equation Material - Nifu, Martha Marsela; Hijriani, Lailin; Simarmata, Justin Eduardo (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
The purpose of this study was to determine that the teacher's Pedagogical Knowledge in utilizing technology by using the GeoGebra application can improve the learning outcomes of junior high school students on the material of straight line equations. This type of research is Classroom Action Research (PTK) conducted in two cycles with the success indicator of 70% classical completeness. The research instruments used include observation sheets and test question sheets, with data collection techniques in the form of written tests and observations. The subjects of this study were students of class VIII A of St. Aloysius Niki-Niki Catholic Junior High School in the academic year 2023/2024, totaling 28 students. The results showed that through Pedagogical Knowledge of teachers in the utilization of technology by using the GeoGebra application can improve the learning outcomes of junior high school students on the material of straight line equations.